Strategic Approaches to International Market Penetration for Local Products - Trisna Rumapea; Antonius Gerarldo (Journal on Economics, Management and Business Technology, 2024)
This research explores the intricacies of international market penetration strategies for local products, aiming to provide comprehensive insights and actionable recommendations for businesses seeking to expand their presence in global markets. Employing a mixed-methods approach, the study integrates qualitative insights from case studies and interviews with quantitative data analysis and literature review to offer a holistic understanding of the subject matter. Through the analysis of case studies on successful and unsuccessful international expansion efforts, the research identifies key patterns, trends, and lessons learned in market selection, adaptation strategies, market entry modes, and competitive analysis. Findings underscore the critical importance of cultural sensitivity, strategic partnerships, and adaptive resilience in achieving success in global expansion endeavors. The synthesis of findings contributes to the advancement of theoretical frameworks in international business literature, validating concepts such as cultural adaptation, strategic partnerships, and regulatory compliance. Furthermore, the research offers practical implications and recommendations for businesses, emphasizing the need for thorough market research, cultural adaptation, strategic partnerships, and adaptive resilience in navigating the complexities of international markets.